Numerical investigation into characteristics of far-field aerodynamic noise radiated by inter-coach space of high-speed maglev trains. (October 2022) - Wang, Rusi; Huang, Jingyu
Self-sustain oscillation leads to aerodynamic noise at inter-coach space. It can be seen from existing literature that the aerodynamic noise at inter-coach space has already become an important branch in the domain of vibration and noise reduction of high-speed wheel-rail trains. However, to the best of our knowledge, approaches focusing on the identical problem that does exist in the windshield area of high-speed maglev train have not yet been published. In this paper, a computational model is established for the inter-coach space of high-speed maglev train running at the speed of 600 km·h −1 . The model includes two half-mid-train with one outer full windshield connected. On the basis of Realizable k-ε model and Spalart-Allmaras DDES model, respectively, the steady and unsteady flow field are initially solved, and the pressure fluctuation on rigid surfaces, the vortex shedding process and the distribution of sound source power are then visualized to make clear the genesis mechanism of aerodynamic noise in the windshield area. With penetrable integration surfaces constructed, the far-field sound radiation is obtained from the Ffowc Williams-Hawkings (FW-H) equation, and the contribution rate of the quadrupole noise sources to the total aerodynamic noise is then calculated as a comparison to the previous conclusions that aerodynamic noise at inter-coach space of high-speed trains was mainly dipole. Of great significance, it is concluded in this paper that at the speed of 600 km·h −1, the quadrupole sound source contributes about 35.6% to the total sound energy in the far field, which is lower than the percentage using the entire train model at the same speed level but still cannot be ignored. The results in this paper are able to provide guidance for future researches on vibration and noise reduction of high-speed maglev train.